Local Food Systems: Making Visible the Invisible Through Urban Agroecology - Pengue, Walter Alberto (Frontiers in Sustainable Cities, 2022)
The world is going through the second wave of urbanization. Although cities still occupy a relatively small area, they are the main consumers of natural resources, energy and water. And in general, they depend for their food, on resources from outside. The economic and bioecological crisis such as the economic one, the social one, pandemics, war or clime change, have faced cities with unexpected problems but also with new perspectives. Likewise, the advance of industrial agriculture nearby urban areas generates other types of impacts. The intensive use of agrochemicals and synthetic fertilizers, especially in developing countries but also in developed countries, impacts the socio-environmental health of urbanites. Making visible the invisible and the immeasurable—through tools such as ecological economics–puts under a comprehensive umbrella, a set of ecological, social and economic aspects that urban societies had not perceived until now such as greening of cities, the recovery of ecosystem services and restoration of “brown lands” or the relevance of food self-sufficiency production. Urban agroecology plays a significant role to reach these ones and begins to be a real possibility to build local food systems and new ways of consumption and networks. This is a particular contribution in times of crises.